The Role of Social Capital in the Development of Native Chicken Enterprises: A Case Study at P4S Laskar Andalas - Putra, Meldy Eka; Helmi; Hasnah (Talenta Publisher, 2024)
This study investigates the increase in native chicken population in Koto Parik Gadang Diateh District of South Solok Regency, credited to the transformation of MFH Farm into Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) Laskar Andalas. The objectives of this study include describing P4S Laskar Andalas' profile and role in native chicken business development and analyzing social capital's impact on the local economy through chicken farming. Using a case study approach, key informants such as P4S Laskar Andalas, KUB PM Koto Parik, native chicken breeders, and local restaurants were engaged. Findings reveal P4S Laskar Andalas' diverse role in native chicken husbandry, including enterprise operation, advisory services, and business partnerships. Strong social bonds between P4S Laskar Andalas, KUB-PM Koto Parik, and breeders indicate robust bonding social capital. Additionally, positive relationships with Sungai Kalu Restaurant and Teras Ayam Kampung Restaurant reflect well on bridging social capital. The strong association between P4S Laskar Andalas and the Agriculture Office of South Solok Regency demonstrates strong linkage social capital. These results underscore social capital's role in facilitating collaborative efforts and enhancing the local economy through native chicken farming.